Political thought in Ireland 1776-1798 republicanism, patriotism, and radicalism - Small, Stephen (Stephen John) (Oxford historical monographs., 2002)
This is an analysis of late-18th-century Irish patriot thought and its development into 1790s radical republicanism. The book is a history of the rich political ideas and languages that emerged from the tumultuous events and colourful individuals of this pivotal period in Irish history.